Advances in Fetal Surgery: Current Challenges and Future Perspectives - Shrivastav, Richa; Bano, Kahkasha; Singh, Ajay Kumar (Journal of Neonatal Surgery, 2025)
In maternal-fetal medicine, fetal surgery has become a game-changer, providing life-saving treatments for congenital defects that were previously thought to be incurable before to birth. The range of fetal interventions has increased because to developments in prenatal diagnostics, imaging modalities, and surgical procedures, which have improved long-term results and survival rates. Spina bifida, congenital diaphragmatic hernia, twin-to-twin transfusion syndrome, and sacrococcygeal teratoma are among the disorders that have been corrected thanks to open fetal surgery, fetoscopic treatments, and minimally invasive approaches. The dangers of preterm labor, complications for both the mother and the fetus, and the technical difficulties of in utero procedures are some of the obstacles that still exist in spite of these developments.Further influencing the development of this discipline are ethical issues pertaining to the autonomy of the mother and fetus, the possibility of fetal death, and the financial strain on healthcare systems. Enhancing minimally invasive procedures to lower maternal risks, developing biomaterials for fetal wound healing, and incorporating gene and stem cell therapy to treat genetic and developmental abnormalities in utero are the main goals of future perspectives in fetal surgery. Developments in regenerative medicine and artificial womb technology also have the potential to completely transform fetal interventions. Fetal surgery has the potential to provide even safer and more effective treatment choices with further study and technology advancement, revolutionizing newborn care and expanding the scope of perinatal medicine.